Voids in network-forming liquids and their influence on the structure and dynamics - Wilson, M; Madden, P; Medvedev, N; Geiger, A; Appelhagen, A (1998)
A Voronoi analysis is applied to clarify the origin of certain unusual physical properties of three representative network-forming ionic liquids: SiO2, ZnCl2, and BeCl2. In each of these fluids, the local structure under ambient pressure comprises a tetrahedral unit of anions around cations which link together to form a network. The Voronoi analysis is used to characterize the empty space (voids) within the network. Despite sharing the same local tetrahedral arrangement, the network properties of the three liquids differ markedly on an intermediate length scale and this leads to significant differences in the properties of the voids. It is shown how the void analysis helps to interpret the anomalous behaviour of the diffusivity in SiO2, which over a certain range of density increases with increasing density, and to clarify the origin of the intermediate range order in the atomic positions, as seen in the much discussed first sharp diffraction peak (or pirepeak) in diffraction data.